Fermented dried Citrus unshiu peel extracts exert anti-inflammatory activities in LPS-induced RAW264.7 macrophages and improve skin moisturizing efficacy in immortalized human HaCaT keratinocytes - Chulwon Kim; Jun Ji; Seung Ho Baek; Jong Hyun Lee; In Jin Ha; Soon Sung Lim; Hong Jae Yoon; Yun Je Nam; Kwang Seok Ahn (Taylor & Francis Group, 2019)
Context: Citrus unshiu Markovich (Rutaceae) peel is known to contain high concentrations of flavonoids and exerts pharmacological effects on antioxidant, anti-inflammation, allergies, diabetes and viral infections. Objective: Very little is known about potential activity of fermented dried Citrus unshiu peel extracts (FCU) using Bacillus subtilis, as well as its mechanism of action. We investigated the effects of FCU on the anti-inflammatory activities in murine macrophages and moisturizing effects in human keratinocytes. Materials and methods: We isolated the Bacillus subtilis from Cheonggukjang and FCU using these Bacillus subtilis to prepare samples. The cells were pre-treated with various extracts for 2 h and then induced with LPS for 22 h. We determined the NO assay, TNF-α, IL-6 and PGE2 in RAW 264.7 ells. The expression of SPT and Filaggrin by FCU treatment was measured in HaCaT cells. Result: We found that two types of FCU highly suppressed LPS-induced nitric oxide (NO) without exerting cytotoxic effects on RAW 264.7 cells (21.9 and 15.4% reduction). FCU inhibited the expression of LPS-induced iNOS and COX-2 proteins and their mRNAs in a concentration-dependent manner. TNF-α (59 and 30.9% reduction), IL-6 (39.1 and 65.6% reduction), and PGE2 secretion (78.6 and 82.5% reduction) were suppressed by FCU in LPS-stimulated macrophages. Furthermore, FCU can induce the production of hyaluronic acid (38 and 38.9% induction) and expression of Filaggrin and SPT in HaCaT keratinocyte cells. Discussion and conclusion: FCU potentially inhibits inflammation, improves skin moisturizing efficacy, and it may be a therapeutic candidate for the treatment of inflammation and dry skin.